БАРБОТАЖЛИ АБСОРБЦИОН АППАРАТИНИНГ ГАЗ УЗАТУВЧИ ТЕШИКЛАРИ ГИДРОДИНАМИКАСИ - Каримов Икромали Тожиматович, Халилов Исмоилжон (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In the article, as a result of theoretical studies, the equation for calculating the value of the height of the gas cushion "h" that ensures equal distribution of the purified gas to the mixing sections of the apparatus and operation in a stable hydrodynamic mode is recommended, and the resistance coefficients of the holes are determined.